Adequacy and timeliness of antenatal care visits among Ethiopian women: a community-based panel study. Issue 12 (23rd December 2021) - Shiferaw, Kasiye; Mengistie, Bezatu; Gobena, Tesfaye; Dheresa, Merga; Seme, Assefa
Abstract : Objectives: The purposes of the study are; (A) to identify whether Ethiopian women's antenatal care (ANC) visits are adequate and timely and (B) to explore factors that determine these. Design: Panel study design. Setting: Ethiopia. Participants: A total of 2855 women nested within 217 enumeration areas. Primary outcome measures: Adequacy and timeliness of ANC visits. Results: Of all the 2855 respondents, 65% had made an ANC visit once, while 26.8% initiated ANC visits in a timely way and 43.3% attended adequate ANC visits. Rural residence (adjusted OR (AOR)=0.55, 95% CI: 0.36 to 0.84), attending higher level of education (AOR=2.64, 95% CI: 1.47 to 4.77), being multipara (AOR=0.53, 95% CI: 0.32 to 0.89) and encouragement by partners to attend clinic for ANC (AOR=1.98, 95% CI: 1.14 to 3.44) were significantly associated with timeliness of ANC visit. Similarly, residing in rural areas (AOR=0.20, 95% CI: 0.12 to 0.35), attending higher level of education (AOR=2.96, 95% CI: 1.38 to 6.15), encouragement by partners to attend clinic for ANC (AOR=2.11, 95% CI: 1.31 to 3.40) and timeliness of ANC visit (AOR=4.59, 95% CI: 2.93 to 7.21) were significantly associated with adequacy of ANC visits. Conclusions: A quarter of the pregnant women started ANC visits during the first trimester and nearly half attended adequate ANC visits with wider disparities across regions of their origin and their background characteristics. Concerted efforts on tailored interventions for rural residents, female education and partner involvement are recommended for early and adequate ANC visit(s).